PENGEMBANGAN MODEL PEMBELAJARAN PARTISIPATIF UNTUK MENINGKATAN PENCAPAIAN PERAN BIDAN SEBAGAI PENDIDIK - Rodiyatun Rodiyatun (Jurnal Penelitian Kesehatan SUARA FORIKES, 2016)
Introduction: In relation to her role as an educator, midwife has a responsibility in guiding healthy behavior and promotion of health program in mothers, children, family planning and reproduction health. Improvement of midwives’ skills at performing his role as an educator can be conducted through participative learning strategy which involves midwives actively in informal learning process. Participative Learning Model is learning activity conducted from knowledge, values and skills owned by learners and emphasizing on problem solving approach. Method: This research employed experiment, pretest-posttest control group design, consisting of two groups, experiment group and control group. Independent variable was participative learning model and dependent variable was midwife’s role as an educator. Data analysis technique used descriptive analysis and it was assumed that this research was conducted on population. Analysis of effects of participative learning model on achievement of midwife’s role as an educator was based on median and mode values of pretest and posttest using Wilcoxon test. Result: There was a percentage increase of achievement in educator’s role which was categorized tolerant in all competence of educator’s role. Wilcoxon test showed that p-value, (0,046) < α (0,05) means that development of participative learning model with observation and reflection had effects on increase of achievement in midwife’s role as an educator for health service in mothers, children and family planning (KB)/reproduction health. Key Words: Educator’s, health education, midwife